Acurácia da técnica de oscilações forçadas na avaliação do controle da doença em pacientes asmáticos graves - Chiabai, Joseane (2019)
Introduction: Asthma is a chronic inflammatory disease of the respiratory tract, which affects both large and small airways. The pathogenesis is very heterogeneous, with distinct phenotypes occurring. Assessing the degree of inflammation of the most peripheral airways has proved essential for a more adequate management, because more distal inflammation is an important factor associated with worse disease control. Spirometry, the most widely used method in clinical practice, can be insensitive in detecting changes in the small airways and in discriminating changes in the state of asthma control. Thus, new tests have been proposed, and analyses of respiratory impedance, using oscillometry technique, have stood out. Aim: The aim of this study was to investigate usefulness of oscillometry - spectral and intra-breath - in subjects with severe asthma to assess disease control and determine the best parameters that detect uncontrolled asthma. Methods: Cross-sectional, exploratory study. Adults with severe asthma were recruited from the asthma reference center of the Santa Casa de Misericórdia de Vitória-ES. Subjects answered a questionnaire and were submitted to spirometry and oscillometry - spectral and intra-breath. Asthma control was verified through Control Test (ACT). A score greater than or equal to 20 points was adopted as indicative of controlled asthma. Statistical analysis was performed using the computing environment R. The statistical significance level was set as p-value < 0.05 for two-tailed tests. Results: Sixty asthmatics were evaluated; the mean age was 56.7 years old. There was a predominance of women (82%), and most (63%) reported onset of asthma symptoms in childhood or adolescence. Subjects with an ACT score of 20 or more and 19 or less were categorized as Controlled Asthma (n=31) and Uncontrolled Asthma (n=29), respectively. There was no difference in age, gender, ethnicity, age of the beginning of asthma symptoms or current pharmacological treatment. Regarding pulmonary function tests, in baseline lung function, there were no differences in the spirometry, between the two groups. Data analysis of the oscillometry technique identifies that uncontrolled asthma was associated with higher resistance (for R8 and R10), more negative reactance (for X6, X8 and X10) and lower respiratory compliance in the spectral analysis (p<0.05). In addition, all parameters in the intra-breath oscillometry showed significant differences between controlled and uncontrolled asthmatics (p <0.01 for RmeanI, ReE, R, XmeanE, XeE, XeI, and X). After short-acting bronchodilator (SABA), there was also no difference in spirometry parameters between the groups. On the other hands, the analysis of oscillometry after SABA showed maintenance of more negative reactance (for X6, X8 and X10) and lower compliance in the spectral phase (p <0.05); and significant differences in intra-breath analysis for RmeanI, ReE, R (p <0.01). The accuracy of the tests in discriminating between controlled and uncontrolled asthma was higher for intra-breath variables (AUC=0.65 to 0.72). Conclusion: The measurement of respiratory impedance by oscillometry has shown increasing clinical utility and, in the present study, it showed to be superior to spirometry in the evaluation of asthma control, especially in intra-breath oscillometry analyses. It is an easy-to-perform technique that provides additional data to spirometry and has the potential to assist in therapeutic decisions.